Differential kinetics of nitrogen oxides reduction leads to elevated nitrous oxide production by a nitrite fed granular denitrifying EBPR bioreactor. Issue 4 (10th February 2020) - Gao, Han; Zhao, Xiaotian; Zhou, Lei; Sabba, Fabrizio; Wells, George F.
Abstract : Batch kinetic assays of DPAO-enriched biomass reveal elevated kinetics when nitrite is supplied for P uptake, but extremely slow kinetics for reduction of the potent greenhouse gas nitrous oxide. Abstract : Denitrifying polyphosphate accumulating organisms (DPAOs) are capable of nitrate (NO3 − ) and/or nitrite (NO2 − ) reduction coupled to phosphorus (P) uptake when subjected to alternating anaerobic/anoxic conditions. However, accumulation of the denitrification intermediate nitrous oxide (N2 O), a potent greenhouse gas, has been previously observed in DPAO enrichments. To date, denitrification capability and denitrifying P uptake rates of DPAOs using different electron acceptors (NO3 −, NO2 −, and N2 O) after long-term exposure and adaptation to elevated concentrations of NO2 − characteristic of shortcut N removal systems have not been examined. To address this knowledge gap, we operated a lab-scale sequencing batch reactor under alternating anaerobic/anoxic conditions with high NO2 − feed for over a year to obtain an enrichment of " Candidatus Accumulibacter phosphatis" capable of denitrifying P uptake. Ex situ batch assays were performed to clarify capacity for reduction of various nitrogen oxides and simultaneous P uptake by the DPAO enrichment culture under both decoupled (internal COD as electron donor) and coupled (external COD as electron donor) feeding conditions. These batch assays revealed distinct nitrogen oxides reduction and denitrifying P uptake capabilities, with significantly elevated kinetics when NO2 − was supplied as the electron acceptor for P uptake. Surprisingly, N2 O reduction was extremely slow when only internal storage polymers were present as an electron donor (decoupled feeding), as is typical for PAOs in practical enhanced biological P removal processes. This pattern held when N2 O was the sole electron acceptor supplied, and when N2 O was supplied with NO3 − or NO2 − . We documented a particularly strong propensity for N2 O accumulation in the presence of NO2 − under both decoupled and coupled scenarios. The formation of granular microbial aggregates in the reactor was observed without intentional granule selection. High-throughput 16S rRNA gene sequencing revealed selective enrichment of putative DPAOs in large granular biomass. qPCR-based profiling of denitrification functional genes demonstrated that smaller floccular aggregates had higher genomic potential for N2 O production, while large granular aggregates likely played a role as a putative sink for N2 O.